Why are more redistributive social security systems smaller? : A median voter approach - Marko Koethenbuerger; Panu Poutvaara; Paola Profeta (Center for Economic Studies and ifo Institute (CESifo), 2005)
We suggest a political economy explanation for the stylized fact that intragenerationally more redistributive social security systems are smaller. Our key insight is that linking benefits to past earnings (less redistributiveness) reduces the efficiency cost of social security (due to endogenous labor supply). This encourages voters who benefit from social security to support higher contribution rates in political equilibrium. We test our theory with a numerical analysis of eight European countries. Our simple, but suggestive median voter model performs relatively well in explaining the stylized fact and cross-country differences in social security contribution rates.
Keywords: D72; H55; 330; earnings-related and flat-rate benefits; social security; public pensions; median voter model; Sozialversicherung; Soziale Sicherung; Einkommensumverteilung; Sozialversicherungsbeitrag; Umlageverfahren; Median Voter; Schätzung; EU-Staaten